Mathematical Analysis of the Effect of Rotor Geometry on Cup Anemometer Response - Ángel Sanz-Andrés; Santiago Pindado; Félix Sorribes-Palmer (The Scientific World Journal)
The calibration coefficients of two commercial anemometers equipped with different rotors were studied. The rotor cups had the same conical shape, while the size and distance to the rotation axis varied. The analysis was based on the 2-cup positions analytical model, derived using perturbation methods to include second-order effects such as pressure distribution along the rotating cups and friction. The comparison with the experimental data indicates a nonuniform distribution of aerodynamic forces on the rotating cups, with higher forces closer to the rotating axis. The 2-cup analytical model is proven to be accurate enough to study the effect of complex forces on cup anemometer performance.